Teoretyzowanie komunikacji - Kulczycki, Emanuel (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2012)
The book contributes to the debate over the issue of the disciplinary status of Communication Studies, which theorizes the Communication Practice. The author attempts to develop an original stance which may be the first step towards the creation of an autonomous Communication Discipline. The work may be also considered a proxy dialogue with Robert T. Craig and his concept of placing the research of communication within the framework of a practical discipline. The attempt to indicate what conditions would enable the Communication Studies to become autonomous is based on the assumption that the studies may only become an independent academic discipline when their basic research subject (i.e. the process of communication) is constituted outside the existing fields of science – when a communication ontology is specified. It requires a redefinition of the research perspective and a modification of the understanding of the relation between theory and practice. Therefore the treatise is mainly concerned with two issues: 1) communication understood as an activity specific to people; 2) considerations over the relative process – discipline of communication – regarded as one of the practical disciplines. In other words, the subject of the work is not the communication process itself, but the system of its scrutiny, a somewhat autonomous discipline, which provides a framework for theorizing the Communication Process (understood as a form of social practice). Such assumptions entail three main aims of the work. They include: 1) displaying the historical and cultural sources of the contemporary approaches to the notion of communication; 2) presentation of the theoretical concepts of Robert T. Craig as a means of dealing with the “lack of communication between the theorists of communication” – metatheory of communication research as a philosophical-methodological foundation of the discipline of communication; 3) demonstrating the philosophical implications stemming from assuming the communication studies to be a practical discipline. The book is not an attempt to delineate and categorize any forms of theorizing of the communication process. It is an endeavour to indicate such a way of conducting research of the relative subject which would serve “a purpose”. The first chapter is devoted to the cultural and historical sources of the contemporary approaches to the notion of communication. It deals with the issues which mainly concern our understanding of the process of communication as an activity specific to people. The chapter focuses on the development and the origin of our understanding of the communication processes and presents two basic approaches towards them: the transmission and the constitutive one. This part of the treatise also contains a presentation of the work’s assumptions and defines its scope. The author uses the Shannon-Weaver transmission model to show that the research of the process of communications may not be limited to the category of transmission, which nevertheless may not be discarded altogether. Its limits need to be overcome while the model should be included in the constitutive approach. In this context it introduces the understanding of the process of communication as a kind of a practice – in its social and individual aspect. The second chapter is devoted to the deliberations over the disciplinary status of the communication studies and presents tentative terminology which may help to constrain the “terminological chaos” found in communication research. Additionally, the main research perspectives of the communication studies are reconstructed on the basis of the work of Juergen Habermas and Arthur P. Bochner. The third chapter begins with a presentation of the origin of the differentiation between practical and theoretical disciplines as well as the sources of the American researcher’s concepts. The introduction of the terminology developed by Thomas Kuhn and transposed to humanities is used to describe what a practical discipline is. It is done by means of two exemplars: the study of the rhetoric and the methodology developed by Abraham Kaplan. An analysis of the practical disciplines’ assumptions precedes the introduction of the differentiation between the first- and the second-order practical disciplines. It is followed by a presentation of basic methodological assumptions of any practical disciplines – according to both Robert T. Craig as well as Polish philosophical thought. The final chapter builds on the first three parts. Based on the research on: communication as a practice, the practical research, communication as a practical discipline, and introducing the Craigian scheme of constituting the research field of the discipline of communication (by means of the critical-deductive and the critical-inductive way), I indicate the conditions which need to be applied to the process of communication in order for it to be perceived as a fundamental subject of analysis of an independent field of science. The considerations included in this book are meant not only to provide basic answers, but also to pose questions – as this is the only way to deliberately and rationally construct a field of public discourse and establish (negotiate) a common view of the world.

Celem tej książki jest próba wskazania podstawowych warunków niezbędnych do wypracowania filozoficznego gruntu dla refleksji nad procesem komunikacji oraz rozważań nad statusem dyscyplinarnym odnośnej refleksji. Realizacja tego przedsięwzięcia wymaga już na wstępie postawienia jasnej i wyraźnej tezy głoszącej, iż refleksja nad procesem komunikacji dopiero wtedy może osiągnąć status autonomicznej dyscypliny akademickiej, gdy będzie uprawiana w perspektywie praktycznej jako jedna z dyscyplin praktycznych. Źródłem postawienia takiej tezy jest niezgoda na sposób ujmowania odnośnej refleksji i jej statusu w ramach nauk(i) o komunikacji. Mowa mianowicie o sytuacji, w której głosimy istnienie samodzielnej dyscypliny naukowej reflektującej nad procesem komunikacji jedynie na bazie założenia, iż wiele subdyscyplin w ramach swoich badań podejmuje zagadnienie komunikacji międzyludzkiej. Brak akceptacji powyższej przesłanki wynika przede wszystkim z braku podejmowania w ramach nauki o komunikacji samoświadomej refleksji metodologicznej, co powoduje natomiast utrzymywanie się wielu sprzecznych poglądów i twierdzeń. To, co badacze określają mianem refleksji komunikacyjnej bądź komunikologicznej, nie stara się szukać swojego ugruntowania. Nie chodzi oczywiście o jakieś transcendentalne, poza kulturowe warunki istnienia praktyk komunikacyjnych, lecz o metodyczną refleksję nad sposobem istnienia komunikacji w ramach kultury oraz refleksji nad narzędziowym charakterem odnośnych praktyk. Książka ta włącza się w trwającą dyskusję dotyczącą problemu dyscyplinarności badań nad komunikacją. Dla polskiego Czytelnika, który nie miał sposobności zapoznania się z publikacjami anglojęzycznymi na ten temat, umiejscowienie tej kwestii na „mapie współczesnej myśli humanistycznej” może być problematyczne, gdyż wśród polskich badaczy podejmujących explicite problem praktyk komunikacyjnych w ramach nauki o komunikacji ciężko odnaleźć nie tylko odniesienie do tego zagadnienia, ale przede wszystkim próbę nawiązania świadomej dyskusji.
Publikacja jest dostępna na licencji Creative Commons Uznanie autorstwa-Użycie niekomercyjne-Bez utworów zależnych 3.0 Polska. Pewne prawa zastrzeżone na rzecz autora. Zezwala się na wykorzystanie publikacji zgodnie z licencją – pod warunkiem zachowania niniejszej informacji licencyjnej oraz wskazania autora jako właściciela praw do tekstu. Treść licencji jest dostępna na stronie http://creativecommons.org/licenses/by-nc-nd/3.0/pl/
Keywords: Communication; Theorizing; Robert T. Craig; Culture; Philosophy; Philosophy of Communication; Communication Studies; Komunikacja; Komunikologia; Komunikacja społeczna; Nauka o komunikacji; Studia nad komunikacją; Filozofia komunikacji; Filozofia; Filozofia kultury; Filozofia humanistyki